Prevalence of stable coronary artery disease and its associated clinical factors among patients with chest pain and elevated cardiac troponin alone. Issue 4 (April 2023) - Kang, Min-Kyung; Shin, Dong Geum; Han, Donghoon; Choi, Seonghoon; Cho, Jung Rae; Lee, Namho
Abstract: Cardiac troponin is a useful test for diagnosing cardiogenic causes in patients with chest pain. However, cardiac troponin levels are often elevated in patients with chest pain due to non-cardiac causes other than coronary artery disease. The purpose of this study was to investigate the prevalence of coronary artery disease (CAD) and its associated factors in patients with chest pain and elevated cardiac troponin I (cTnI). 104 patients (mean age, 65 ± 11 years; 60 [58%] men) who underwent coronary angiography (CAG) for chest pain and elevated cTnI levels were enrolled in this study. All patients had a normal CK-MB range and did not show any ischemic changes on electrocardiography or echocardiography. Patients were classified into two groups according to the presence of CAD (Group 1, n = 62) and the absence of CAD (Group 2, n = 42). Patients were classified into subgroups according to the presence (Group 2a, microvascular angina [MVA], n = 18) and absence (Group 2b, non-angina [NA], n = 25) of angina. CAD was diagnosed in 62 (60%) patients and MVA was suspected in 18 (17%) patients without CAD. Patients with CAD showed elevated blood pressure and slightly decreased heart rate. Diabetes mellitus was more prevalent in patients with CAD and patients without CAD (esp. with MVA) were more likely to be common drinkers. Increased relative wall thickness (RWT) and reduced E' velocity were associated with CAD. High-density lipoprotein (HDL) levels were reduced in patients with CAD and MVA but were higher in patients with NA. Lower HDL level was found to be independently associated with the presence of CAD. Elevated cTn1 levels without other evidence of myocardial ischemia are sufficient for performing CAG in patients with stable chest pain.